2006
DOI: 10.1128/aem.00956-06
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Antibiotic Sensitivity of Listeria monocytogenes Strains Isolated from Oysters, Fish, and Estuarine Water

Abstract: We analyzed the presence of Listeria spp. in oyster, fish, and seawater samples and tested isolates for antibiotic sensitivity. Listeria monocytogenes was found in 4.5% of fish samples and 8.3% of seawater samples and was not recovered from oysters. Multiresistant environmental strains were found, representing a potential threat to human health.Human listeriosis is a public health problem of low incidence but high mortality, requiring prompt diagnosis and adequate antibiotic therapy (1). Over the last 2 decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 18 publications
9
40
1
2
Order By: Relevance
“…The environmental isolates were also susceptible to other antimicrobials tested. Although l. monocytogenes is commonly susceptible to a wide range of antimicrobials, some authors have reported tetracycline resistance in environmental strains of l. monocytogenes (MacGowan et al 1994) or multidrug resistance to ampicillin, erythromycin, tetracycline, dicloxacillin, and co-trimoxazole (Rodas-Suárez et al 2006). The monitoring of l. monocytogenes resistance to antimicrobials is currently needed as well as the development of international criteria for the evaluation of resistant strains.…”
Section: Resultsmentioning
confidence: 99%
“…The environmental isolates were also susceptible to other antimicrobials tested. Although l. monocytogenes is commonly susceptible to a wide range of antimicrobials, some authors have reported tetracycline resistance in environmental strains of l. monocytogenes (MacGowan et al 1994) or multidrug resistance to ampicillin, erythromycin, tetracycline, dicloxacillin, and co-trimoxazole (Rodas-Suárez et al 2006). The monitoring of l. monocytogenes resistance to antimicrobials is currently needed as well as the development of international criteria for the evaluation of resistant strains.…”
Section: Resultsmentioning
confidence: 99%
“…monocytogenes is widespread in the environment and commonly occurs in surface waters (Colburn et al, 1990;Wilkes et al, 2011) which will consequently contaminate estuarine and coastal waters (Beleneva, 2011;Bou-m'handi et al, 2007;Colburn et al, 1990;El-Shenawy and El-Shenawy, 2006;El Marrakchi et al, 2005;Hansen et al, 2006;Rodas-Suarez et al, 2006;Rorvik et al, 1995). Consumption of contaminated processed fish and shellfish has been associated with transmission of infection (Brett et al, 1998;Ericsson et al, 1997;Facinelli et al, 1989;Farber et al, 2000;Lyytikainen et al, 2006;Misrachi, 1991;Mitchell, 1991;Riedo et al, 1994;Tham et al, 2000).…”
Section: Data Linking Presence In Seawater To Food-borne Illnessmentioning
confidence: 99%
“…Although most isolates of L. monocytogenes and other Listeria spp. are susceptible to antibiotics active against gram-positive bacteria, there are several reports on the occurrence of antibiotic resistance in L. monocytogenes isolated from a variety of food items such as dairy, meat, and seafood products (5,(15)(16)(17). Since the food origin of human listeriosis is now recognized, the presence of antimicrobial-resistant L. monocytogenes strains in foods may be of public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterium has been isolated from molluscan shellfish and especially mussels, which are filter feeders and notoriously liable to become contaminated with pathogenic bacteria such as Listeria derived from polluted aquatic environments (4,5). Compared with other food products, very few studies have been carried out on the prevalence of L. monocytogenes in mussels (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation